Vietnam: The Unique Case of For-Profit Monopoly - Chau, Quang (International Higher Education, 2020)
In 2006, the Vietnamese state made a policy unique in global private higher education (PHE), when it mandated that all nonprofit private universities convert to for-profit. This U-turn decision in effect acknowledged the widespread reality that nonprofit institutions were in fact distributing profits to owners. The state has recently legalized the nonprofit form, but many critics have doubts about how nonprofit the emergent nonprofit form will be.